Pengembangan Multimedia Pembelajaran Interaktif Berbasis Articulate Storyline 3 pada Materi Aritmetika Sosial Siswa Kelas VII SMP Negeri 12 Merangin - Jainuri, Muhammad; Susanti, Ade; Awatif, Awatif; Yohanes, Yohanes (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
This study aims to develop interactive learning multimedia based on articulate storyline 3 on social arithmetic material for class VII students of SMP Negeri 12 Merangin which is valid, practical, and effective. This study uses research and development methods with the APPED model. These interactive learning multimedia was validated by five experts. Validity is seen from the validation sheet, the practicality of the response sheet and student interviews, and the effectiveness of learning outcomes and student learning activities. The results showed that the average score for the validation of mathematicians was 4.22 with a very valid category, Indonesian language experts 3.88 with a very valid category, media experts 4.78 with a very valid category, and teacher validation. mathematics 4.80 with a very valid category. The overall validity score is 4.58 with a very valid category. The proportion of students' responses was 82.27% in the practical category. The percentage of classical learning outcomes is 77.3% in the effective category and the average percentage of student activity is 68.64% in the active category. Based on the results of research and development, it was stated that interactive learning multimedia was valid, practical, and effective.